360-degree Cervico-Dorsal Fixation througha Single Posterior Approach in a 19 years Old Male with Expansile Bone Mass: A Case Report - Chowdhury, Dhiman; Rahman, Atikur; Khan, Robert Ahmed; Rahman Sikder, Md Shahidur; Amin, Firoj Ahmed Al; Ahmmed, Tayeb; Husna, Asma Ul; Islam, Md Ariful (Bangladesh Journal of Neurosurgery, 2022)
Cervico-Dorsal junction is a transitional zone of spinal column. 360-degree fixation of cervico-dorsal region in a single posterior approach is a difficult and challenging procedure accounting the spinal cord decompression, posterior vertebral body replacement and then posterior instrumentation. Here we have described a patient who presented with features of spastic paraparesis and lower motor palsy of right upper limb due to anexpansile bone mass on Rt side of cervico-dorsal region. He underwent neuronal decompression and 360-stabilisation in a single posterior approach. We review clinical and radiographic features of the patient; the procedureunderwent as well as current other treatment options with reference to the relevant literatures. Bang. J Neurosurgery 2022; 11(2): 122-127